Patterns of Post-socialist Urban Development in Russia and Germany - Gerten, Christian; Boyko, Dmitry; Fina, Stefan (Frontiers in Sustainable Cities, 2022)
Since 1990, urbanization in post-socialist countries has frequently resulted in a loss of urban density in the existing building stock while land use patterns at the outskirts of growing city regions began to sprawl. Formerly state-planned and controlled housing forms as well as industrial and business enterprises were suddenly exposed to new market interests and finance-led investments in a globalizing world. In the initial adaptation to socio-economic transformation pressures after the fall of the iron curtain, the countries in question took different approaches in the governance of urbanization trends. The comparison of urban development between Russian and Eastern German city regions showcases two contrasting examples. Urban development in Russian city regions is largely driven by action-oriented political control of land market interests on the project level. Today's Eastern German city regions have adopted the spatial planning regime of former West Germany. Where the German planning regime aims to coordinate long-term planning and decision-making between different tiers of government with an emphasis to empower land use management on the local community level, land use decisions in Russia are formally free of such regulatory frameworks. According to urban metrics that monitor the sustainability of urban development, both approaches result in increasing urban sprawl and related potential adverse impacts on multiple public goods. Experts interviewed for this article frequently attribute this outcome to “catch-up development” that prioritizes economic development over other land use interests. The cumulative negative effects of urban sprawl on land use efficiency are increasingly being recognized, but they are still frequently subordinate to urban development interests.